INVESTASI YANG BERESIKO DALAM PASAR MODAL - Mutia Evi Kristhy; Dimas Prayoga; Juan Rios Ekaharap; Gabriel Batistuta (Jurnal Komunikasi Hukum, 2022)
The capital market is a place where companies seek funds to finance their business activities. In addition, the capital market is also an effort to raise public funds directly by investing funds into healthy and well-managed companies. The main function of the capital market is as a means of capital formation and accumulation of funds for financing a company/issuer. The presence of capital market institutions in Indonesia adds a row of alternatives for people who have excess funds and are interested in investing to invest their funds. capital. Keywords ; Risk, Investment and Capital Market Abstract The capital market is a place where companies seek funds to finance their business activities. In addition, the capital market is also an effort to raise public funds directly by investing funds into healthy and well-managed companies. The main function of the capital market is as a means of capital formation and accumulation of funds for financing a company/issuer. The presence of capital market institutions in Indonesia adds a row of alternatives for people who have excess funds and are interested in investing to invest their funds.